Dihydroartemisinin targets the miR-497-5p/SOX5 axis to suppress tumor progression in non-small cell lung cancer - Yin, Qing-Hua; Zhou, Qiang; Hu, Jian-Bing; Weng, Jie; Shen, Er-Dong; Wen, Fang; Liu, Song-Lian; Yin, Lei-Lan; Tong, Ya-Jun; Long, Ling; Tang, Ke-Wei; Bai, Si-Te; et al. (Frontiers in Pharmacology, 2025)
IntroductionNon-small cell lung cancer (NSCLC) remains a lethal malignancy with limited therapeutic options. Although dihydroartemisinin (DHA) exhibits anticancer properties, its mechanisms in NSCLC are incompletely understood. This study investigated the role of the miR-497-5p/SOX5 axis in mediating DHA’s effects on NSCLC.MethodsIn vitro experiments utilized A549 and H1299 cells treated with DHA (50 μM). Proliferation, migration, invasion, and apoptosis were assessed. miR-497-5p and SOX5 expression was modulated via genetic silencing. In vivo, A549 xenograft tumor growth in mice was evaluated under DHA treatment (25/50 mg/kg).ResultsDHA significantly suppressed proliferation, migration, and invasion while inducing apoptosis in vitro. Mechanistically, DHA upregulated miR-497-5p and downregulated SOX5—overexpressed in clinical NSCLC. Silencing miR-497-5p attenuated DHA’s effects and increased SOX5, whereas SOX5 knockdown reversed miR-497-5p inhibition. In vivo, DHA dose-dependently inhibited tumor growth with miR-497-5p elevation and SOX5 suppression, effects abrogated by miR-497-5p inhibition but rescued by SOX5 knockdown.DiscussionDHA exerts antitumor activity by activating the miR-497-5p/SOX5 axis, revealing a novel mechanism. Bridging efficacious in vitro concentrations with clinically achievable dosing remains essential for therapeutic translation.